International networking for sexuality education: a politically sensitive subject - Steinhart, Katharina; von Kaenel, Andreas; Cerruti, Stella; Chequer, Pedro; Gomes, Rebeca; Herlt, Claudia; Horstick, Olaf (Sex Education: Sexuality, Society and Learning, 2013)
In 2007, six countries (Argentina, Brazil, Chile, Paraguay, Peru and Uruguay) commenced work on a project to harmonise public policy on school sexuality education (SE) and the prevention of HIV. Inter-sectoral management committees for SE involving ministries of education, ministries of health and civil society were established, national policies and work plans were formulated and implemented, and SE/HIV prevention activities were carried out. The strengths and weaknesses of implementation were assessed. After this, the beginnings of a community of practice were created, with national focal points. This paper analyses the above process using qualitative data generated through semi-structured questionnaires and interviews, with a focus on the perceived contribution of regional collaboration to the development of national policies, national curricula and implementation. Overall, the initiative reached 83,000 teachers and 1,500,000 pupils. Training materials and national curricula and policies were developed, introduced and implemented. Regional collaboration improved political institutionalisation, information exchange, inter-sectoral collaboration, civil society participation, programme legitimacy and the perception of SE as a young person's right. The initiative offers a model for other countries, with regional collaboration helping to establish the case for SE both normatively and institutionally at the political level, mitigate obstacles in the context of such a politically sensitive topic as SE and provide a forum for discussion and the exchange of information which in turn helped legitimise and operationalise national SE policies.